GAMBARAN FAKTOR RISIKO KEJADIAN LEPTOSPIROSIS DI KABUPATEN BOYOLALI (Deskription of Leptospirosis’ Risk Factor In Boyolali Regency) - Wiwid Royanialita; Mateus Sakundarno Adi; Sri Yuliawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The purpose of this research is to describe the incidence of risk factors for leptospirosis in Boyolali district in January 2015 to May 2016. The study is a descriptive observational with cross sectional approach. This study was conducted in 7 District in Boyolali in July-August 2016. Samples were taken of patients with leptospirosis of 20 people with imported cases is exclusion criteria. The results of this study illustrate leptospirosis risk factors include the presence of sewers, wastewater disposal, garbage disposal facilities, the existence of animals at risk, the presence of rodents and the use of personal protective equipment.